Հոգեգալստականների փրկաբանութեան որոշ հարցերի շուրջ - Նարեկ Սրկ․ Կիրակոսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Со времени основания христианской Церкви ее внутренний покой нарушался различными способами, как внешними еретическими направлениями, так и различными раскольническими движениями, которые брали свое начало в Церкви. Они появлялись особенно в странах, которые политически, экономически и религиозно были нестабильны. Секты так же стары, как и Церковь, то есть их существование было обусловлено существованием Церкви, от которой они постоянно питались и искажали Ее православное учение. Since the foundation of the Christian Church, her inner peace was disturbed in various ways, both by external heretical movements and by various schisms that originated inside the Church. They appeared especially in countries that were politically, economically and religiously unstable. Sects are as old as the Church, i.e. their existence was determined by the existence of the Church: they kept being nourished by the Church and distorting her Orthodox teachings. Basically, the Christ they preach has nothing to do with the Orthodox concept.
Keywords: The Bible